Characterisation and structure analysis of taxanes‐loaded human serum albumin nanoparticles prepared by self‐assembly method. (1st August 2018) - Fang, Ru; Wang, Yanbin; Liu, Bentong; Qian, Hua; Yang, Shaozong
Abstract : In this work, human serum albumin (HSA) was used to prepare core‐shell taxanes‐loaded nanoparticle (NP) by self‐assembly method. Various experimental technologies were used to character two different taxanes‐loaded HSA NPs and analyse the structure of them. The obtained NPs had a spherical morphology and core‐shell structure. The data revealed that one paclitaxel (PTX)‐loaded HSA NP (∼40 nm) consisted of six HSA molecules and 34 PTX molecules, and one docetaxel (DOC)‐loaded HSA NP (∼30 nm) consisted of five HSA molecules and 40 DOC molecules. The infrared, three‐dimensional fluorescence and ultraviolet absorption spectra showed that intermolecular hydrogen bond occurred between taxanes and polypeptide chain of HSA and resulted in change of its secondary structure. The fluorescence spectra experiment results suggested that PTX and DOC interacted with tryptophan (Trp)‐214, which lie on site I of HSA, and the type of interactions were hydrogen bond and hydrophobic interaction, respectively. It suggested that the binding mode of taxanes with Trp‐214 is the primary factor that determined the size and loading capacity of taxanes‐loaded HSA NPs. This work indicates that such HSA NP is very promising in the field of nanoscale drug delivery systems research.